Faithless in death - Robb, J. D., 1950- (New York : St. Martin's Press, 2021)
"Gwen Huffman is wealthy, elegant, comforted by her handsome fiancé as she sheds tears over the trauma of finding the body but why did it take an hour to report it? And why is she lying about little things?"--
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Women detectives -- New York (State) -- New York -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction